MANAJEMEN PASAR TRADISIONAL BERBASIS WEB DI KABUPATEN JEMBRANA - I Gusti Putu Suwiarta Aquariawan (Journal of Applied Management and Accounting Science, 2020)
Traditional markets play a very important role in the economic activities of the community, especially for sellers of products of basic necessities produced by small and medium-sized and micro economic actors. The development of information technology as we know it is growing rapidly. It would be very beneficial if the Jembrana district government could take advantage of the current information technology to support the data and information needs of traditional markets in the Jembrana district. This study provides a solution for data processing and information on traditional markets in Jembrana district, namely the traditional web-based market management. With this system, it is hoped that Market Managers in Jembrana Regency can manage and manage the market more professionally with the help of information technology. In addition, this system also serves as information about traditional markets to the public consisting of market location map information, the latest information on market PDs, as well as information on price updates of goods from each market PD in all Jembrana district.